2016
DOI: 10.1115/1.4032338
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Design Parameters on a Double Serpentine Convergent Nozzle

Abstract: Serpentine nozzles are supplied in stealth bombers and unmanned aerial vehicles (UAVs) to evidently suppress the infrared radiation signatures (IRSs) emitted by engine exhausts. It is commonly known that excessive geometric parameters are included in the double serpentine nozzle design and, as a result, the aim of this paper is to study the influences of the design parameters on the performance of double serpentine nozzle. To this end, the design method of the serpentine nozzle was concisely introduced, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…SST κ–ω with compressible effect validated by the experimental data in Sun et al. 21 was chosen as the turbulent model. The predictions of wall pressure, flux rate, and axial thrust were used to validate the turbulent model, as seen in Figure 4.…”
Section: Geometric Model and Numerical Simulation Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…SST κ–ω with compressible effect validated by the experimental data in Sun et al. 21 was chosen as the turbulent model. The predictions of wall pressure, flux rate, and axial thrust were used to validate the turbulent model, as seen in Figure 4.…”
Section: Geometric Model and Numerical Simulation Methodologymentioning
confidence: 99%
“…This variation tread of Ma distribution around the second inflection is different from that in the previous work. 20,21 In the previous work, just the curvature radius around the second inflection is changed with the variety of geometry parameters, and thus the variation tread of Ma distribution is monotonous. However, both the curvature and the duct height are changed with the variety of AR in this paper.…”
Section: Influence Of Aspect Ratio On Serpentine Nozzlementioning
confidence: 95%
See 1 more Smart Citation
“…The flow direction vortex, heat mixing efficiency and wall temperature distribution of S-nozzle with asymmetric lobe mixer were studied by Liu and Du. 10 – 13 Local acceleration and transvers flow features were also shown by Sun, 1416 in which the influence of geometric parameters on the flow characteristics of convergent S-nozzle was investigated. And the results showed that even if the nozzle pressure ratio was lower than the critical pressure ratio, local supersonic region and shock wave was still induced in the convergent S-nozzles due to large curvature.…”
Section: Introductionmentioning
confidence: 91%
“…It showed that two-equation standard k − ε turbulence is accurate to reveal the aerodynamic performances. A further study of Sun et al [14] presented a range of values of some important parameters for achieving better aerodynamic performances. Cheng et al [15] investigated the influences of the shield ratio on the infrared signature for the serpentine nozzle.…”
Section: Introductionmentioning
confidence: 99%